Analgesic efficacy of Intraoperative lidocaine infusion in patients undergoing thyroidectomy - Akgul, Emrah; Gozeler, Mustafa Sitki; Kars, Ayhan; Sahin, Abdulkadir; Ates, Irem (FapUNIFESP (SciELO), 2023)
A significant proportion of patients may experience moderate pain requiring treatment in the postoperative first 24 h following thyroidectomy. The aim of this study was to investigate the evaluation of postoperative patient-reported pain from intraoperative intravenous infusion of lidocaine in patients undergoing thyroidectomy surgery.A total of 40 patients with American Society of Anesthesiologists physical status classifications I and II, aged 18-65 years, who were scheduled for elective thyroidectomy with the same indications under general anesthesia at the Ataturk University Medical Faculty's Ear, Nose, and Throat Clinic between November 2019 and February 2020, were divided into two equal groups as randomized and double-blind. Before induction of anesthesia, patients in the lidocaine group were given 1.5 mg/kg lidocaine IV bolus infusion during the operation and until the end of the first postoperative hour, followed by a continuous infusion of 1.5 mg/kg/h. Patients in the control group were given 0.9% isotonic solution according to the same protocol. In the postoperative period, 50 mg of dexketoprofen trometamol was administered and repeated every 12 h. Postoperative pain scores, additional analgesia, and side effects were recorded.Postoperative pain scores were significantly lower in the lidocaine group (n=20) compared to the control group (n=20) at 30 min and 1st, 2nd, 4th, 8th, and 12th h postoperatively (p < 0.05). Additional analgesia requirements were also significantly lower in the lidocaine group than in the control group (p<0.05).We recommended the use of intravenous lidocaine infusion intraoperatively in thyroidectomy surgery as it reduces pain scores.
Keywords: Analgesics; Pain, Postoperative; Pain; Lidocaine; Analgesics, Opioid; Double-Blind Method; Thyroidectomy; Humans; Original Article; Anesthetics, Local; Infusions, Intravenous; 3. Good health